Permasalahan Sosial Anak Usia Sekolah Dasar - Hafidz Pradita; Fatkhia Nur Azizah; Sofia Nanda Saputri; Dina Puspita Anggraini; Sri Suwartini (Pusat Riset dan Inovasi Nasional, 2025)
Social problems are defined as a cultural or societal inconsistency that endangers the life of a social group or prevents the achievement of the basic desires of the members of the social group, resulting in damage to social relations. In normal situations, there is integration and appropriate conditions in the relationship between these elements, clashes occur, social relations will be disrupted, which can cause instability in group life. Everyone must be aware of their responsibilities as members of the community group when interacting with others. The social process itself cannot run well if there is no personal awareness. Children's interactions with others, including parents, siblings, playmates and the community as a whole are called social development. Learning to recognize the rules and norms in a community is known as social development. Children can identify social and emotional disorders as a focal point. Parents, teachers, and the general public hope to have children who are physically and mentally healthy. It is very pleasant to see children playing happily, clever, diligent in learning and working and free and agile in expressing their ideas and creativity.